METODE BERMAIN PERAN SEBAGAI STIMULASI ASPEK PERKEMBANGAN KOGNITIF ANAK AUTIS USIA 5-6 TAHUN - Simanjuntak, Anita Roslina; Novita, Zarrin (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2024)
Cognitive development in autistic children aged 5-6 years does require the provision of appropriate stimuli, according to the stages of age and level of symptoms experienced by the child. One method that can be applied to children with autism to develop cognitive aspects of children is the method of role playing. Role playing activities can improve children's cognitive development. The purpose of this study was to determine the application of the role playing method as a stimulation of the cognitive development of autistic children aged 5-6 years. The research approach used is qualitative with the method of literature review or literature study relating to relevant theories, as well as supporting articles in the formulation of research problems. The results of the application of role playing performed on children with autism can stimulate aspects of cognitive development at the age of 5-6 years. In conclusion, the role playing method can affect children's cognitive development by providing a gradual stimulus and according to the child's needs.